An open ocean record of the Toarcian oceanic anoxic event - Gröcke, D.; Hori, R.; Trabucho-Alexandre, J.; Kemp, D.; Schwark, Lorenz (2011)
Oceanic anoxic events were time intervals in the Mesozoic characterized by widespread distribution of marine organic matter-rich sediments (black shales) and significant perturbations in the global carbon cycle. These perturbations are globally recorded in sediments as carbon isotope excursions irrespective of lithology and depositional environment. During the early Toarcian, black shales were deposited on the epi- and pericontinental shelves of Pangaea, and these sedimentary rocks are associated with a pronounced (ca. 7 ‰) negative (organic) carbon isotope excursion (CIE) which is thought to be the result of a major perturbation in the global carbon cycle. For this reason, the lower Toarcian is thought to represent an oceanic anoxic event (the T-OAE). If the TOAE was indeed a global event, an isotopic expression of this event should be found beyond the epi- and pericontinental Pangaean localities. To address this issue, the carbon isotope composition of organic matter (s 13Corg) of lower Toarcian organic matter-rich cherts from Japan, deposited in the open Panthalassa Ocean, was analysed. The results show the presence of a major (6 ‰) negative excursion in s 13Corg that, based on radiolarian biostratigraphy, is a correlative of the lower Toarcian negative CIE known from Pangaean epiand pericontinental strata. A smaller negative excursion in s 13Corg (ca. 2‰) is recognized lower in the studied succession. This excursion may, within the current biostratigraphic resolution, represent the excursion recorded in European epicontinental successions close to the Pliensbachian/Toarcian boundary. These results from the open ocean realm suggest, in conjunction with other previously published datasets, that these Early Jurassic carbon cycle perturbations affected the active global reservoirs of the exchangeable carbon cycle (deep marine, shallow marine, atmospheric). © 2011 Author(s).